2022
DOI: 10.3390/polym14183905
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polycarboxylic Grinding Aid on Cement Chemistry and Properties

Abstract: In view of the disadvantages of polycarboxylic acid grinding aids, such as poor reinforcement effect and cumbersome synthesis process, a new type of polycarboxylic acid grinding aid was prepared to meet the requirements of multifunctional admixture for cement concrete. The polycarboxylate grinding aid (PC) was prepared using acrylic acid, sodium allyl sulfonate, and isoprenol polyoxyethylene ether (TPEG) as raw materials, and ammonium persulfate as initiator in the nitrogen atmosphere. The effect of PC and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Yang et al [19] studied polymer-based additions to improve the grindability of cement. They showed that the polymer-based grinding aid increases the specific surface, prevents agglomeration and ball coatings, and improves the roundness, fineness and fluidity of the ground cement.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al [19] studied polymer-based additions to improve the grindability of cement. They showed that the polymer-based grinding aid increases the specific surface, prevents agglomeration and ball coatings, and improves the roundness, fineness and fluidity of the ground cement.…”
Section: Introductionmentioning
confidence: 99%